2019
DOI: 10.1148/radiol.2019190064
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Wave Dispersion Slope from US Shear-Wave Elastography: Detection of Allograft Damage after Liver Transplantation

Abstract: Background: Allograft damage (hepatic parenchymal damage) after liver transplant is associated with the degree of necroinflammation in graft liver. According to a recent animal study, shear-wave dispersion slope obtained at US shear-wave elastography (SWE) is associated with necroinflammatory activity in the liver. Purpose:To evaluate the role of shear-wave dispersion slope in detecting allograft damage after liver transplant. Materials and Methods:In this prospective study, 104 liver transplant recipients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 25 publications
3
69
0
1
Order By: Relevance
“…A significantly higher mean Vi PLUS value was found in COVID-19 patients with pulmonary injury (1.74 ± 0.28 vs. 1.64 ± 0.25, p < 0.0009) in our study. While inflammation plays a pivotal role in the development and progression of liver fibrosis, the non-invasive assessment of inflammation has been studied in past years, with promising results [ 32 , 33 , 34 , 35 , 36 , 37 ]. Several preliminary studies have shown that viscosity might be a useful parameter in tissue characterization, and it might help to detect necroinflammation in the liver [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher mean Vi PLUS value was found in COVID-19 patients with pulmonary injury (1.74 ± 0.28 vs. 1.64 ± 0.25, p < 0.0009) in our study. While inflammation plays a pivotal role in the development and progression of liver fibrosis, the non-invasive assessment of inflammation has been studied in past years, with promising results [ 32 , 33 , 34 , 35 , 36 , 37 ]. Several preliminary studies have shown that viscosity might be a useful parameter in tissue characterization, and it might help to detect necroinflammation in the liver [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the fast Fourier transform algorithm, each displacement caused by shear waves can be transformed from the time domain to the frequency domain. Finally, from shear wave speed and frequency, SWD can be estimated as a phase domain, and is calculated in units of (m/sec)/kHz [8,11]. Since 2D-SWI was introduced, several preliminary studies have reported the clinical significance of SWD in various hepatic diseases, both in a rat model and in human patients [8,11,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, using a rat model, shear wave speed was found to be strongly correlated with lobular inflammation of the liver, whereas dispersion was significantly associated with tissue necrosis [8]. Recently, a few preliminary studies have provided support for the correlation between necroinflammation and dispersion in human liver tissue [11]. However, to our knowledge, no studies have been published or preliminary results reported about both stiffness and dispersion, except in liver cirrhosis or steatohepatitis.…”
Section: Introductionmentioning
confidence: 90%
“…Although SWE reflects both elasticity and viscosity (i.e., viscoelasticity) [22]. SWD is calculated based on SWD measurements and reflects viscosity only [24,25]. Since liver fibrosis advances gradually as hepatitis progresses [26], SWD may be able to estimate liver damage in an earlier stage than SWE.…”
Section: Introductionmentioning
confidence: 99%